Educação pela dureza: um elo de ligação entre autoridade e autoritarismo - Lemos, José Roberto (2005)
The present work search to contribute with the reflections about the authority and pedagogic authoritarianism, as well as the call " severe education" that in a certain way, they almost always had presents in the educational ambit, because this suggests different hierarchical positions, that is to say, on a side the students and on the other the teachers. It is in that complex relationship, that involves many variables, which we tried to penetrate to obtain subsidies that, the relationship of the authority conceptions/concepts and pedagogic authoritarianism could clear up, as well as its influence in the daily of class room. For so much we were worth ourselves of a field research that tried to investigate these conceptions, as well as its relationships, between students and ex-students (now teachers of basic school) of the Course of Pedagogy of UFSCar (Federal University of São Carlos). Our analyses leaned on mainly in the studies facts done by the Critical Theory and in its largest representative's Theodor W. Adorno ideas, and others. The thematic approach was configured in four chapters: the first of them looked for to emphasize the education conceptions for Adorno and the critic to the severe education; in the second we looked for to emphasize the several conceptions on authority and authoritarianism,and the period in which the UFSCar was founded; in the third the university while authoritarian institution; in the fourth and last chapter the analysis of the field research as contribution for the elucidation of the authority conceptions and authoritarianism, as well as the influences in the relationships between students and ex-students (now teachers of basic school) of the Course of Pedagogy of UFSCar.